Facilitating and hindering factors of personal recovery in the context of Soteria—A qualitative study among people with (early episode) psychosis - Leendertse, Pien; Hirzalla, Fadi; van den Berg, David; Castelein, Stynke; Mulder, Cornelis Lambert (Frontiers in Psychiatry, 2023)
Objective: The objective of this study was to gain insight into patients ‘experiences of how personal recovery (PR) is facilitated or hindered in the context of an early episode psychosis setting (Soteria). We thereby aimed to contribute to the understanding of how care settings may promote or hinder the process of PR in people with (acute) psychosis. Method: This study used a qualitative method, consisting of semi-structured in-depth interviews with people who had been admitted to a Soteria-house in the Netherlands. Interview transcripts were analysed following the grounded theory approach. Results: Five themes emerged from the data illustrating how Soteria facilitated or impeded PR. The experience of togetherness in contact with staff and peers, feeling at home, and being active facilitated PR, while the emphasis put on medication by staff was experienced as hindering, and attention for spirituality was missed. Conclusion: In addition to literature that identified factors associated with PR in psychosis, the current study gives a sense of how this can be put into practice. By offering treatment within a normalizing, holding environment, with emphasizing on equality, close contact, optimism, and active structured days, open-mindedness towards spirituality and the role of medication, PR can be facilitated without detracting from- guideline-based treatment aimed at symptomatic recovery. Similarities with existing concepts are discussed.